Culture of Escherichia coli and Related Bacteria. Issue 15 (9th November 2017) - Riley, Sean P.; Woodman, Michael E.; Holt, Jonathan; Stevenson, Brian
Abstract: This appendix provides general techniques, equipment, and media used for the growth of many commonly encountered bacteria. For specific growth conditions, readers should refer to units regarding the laboratory maintenance of the organism of interest. © 2017 by John Wiley & Sons, Inc.